(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Food terminology constitutes an essential component of linguistic systems and serves as a powerful medium of cultural communication. It reflects national traditions, historical development, social values, and patterns of everyday life. This article explores the importance of food terminology in cultural communication through a comparative analysis of the English and Uzbek languages. The study focuses on linguocultural features, symbolic meanings, national specificity, and translation issues related to food-related lexical units. The findings demonstrate that food terminology functions not only as a naming system but also as a cultural code that facilitates intercultural understanding and preserves cultural identity.